A retrospective analysis of respiratory virus transmission before and during the COVID-19 pandemic in Pune the western region of India - Bhardwaj, Sumit; Choudhary, Manohar Lal; Jadhav, Sheetal; Vipat, Veena; Ghuge, Rohan; Salvi, Sonali; Kulkarni, Rajesh; Kinikar, Aarti; Padbidri, Vikram; Bafna, Sanjay; Bavdekare, Ashish; D'costa, Pradeep; et al. (Frontiers in Public Health, 2022)
Background SARS-CoV-2 was first reported in China in December 2019 and quickly spread across the world. Non-pharmaceutical interventions (NPIs) are the key to control the transmission of respiratory viruses. To stop the spread, NPI is widely recommended and is still followed by most countries. Methods At the National Influenza Center of the Indian Council of Medical Research-National Institute of Virology (ICMR-NIV), the surveillance of severe acute respiratory illness and acute respiratory illness cases for influenza and other respiratory viruses is in place. In this study, we analyzed surveillance data on respiratory viruses and/or SARS-CoV-2 testing from January 2017 to December 2021. Multiplex real-time PCR was used to detect the respiratory viruses. Results Our findings indicate that during the pandemic, the positivity for influenza A and B, metapneumovirus, parainfluenza virus, respiratory syncytial virus, and human coronavirus declined significantly. Conclusion The annual distinct seasonal outbreaks of influenza, RSV, and other respiratory viruses as observed during the pre-COVID-19 period were not observed during the COVID-19 pandemic in years 2020 and 21. Social distancing, lock-downs, and non-pharmaceutical interventions may play an important role in the reduction of respiratory viruses. Understanding the seasonal respiratory virus decline could help public health experts prepare for future respiratory virus pandemics.